Analisis SWOT Strategi Marketing Produk Kartu Kredit Bank Mandiri KCP Surabaya Darmo Indah - Anneke Shierly Frycillia Widodo; Citra Cerya Mulya Dewi; Hariyanto Hariyanto; Samsi Rahayu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The development of the banking industry in Indonesia has accelerated rapidly, supported by advances in digital technology that have intensified competition among banks. Consequently, banks are required to continuously adapt by formulating marketing strategies that align with market conditions and customer profiles in order to increase sales. This study finds that credit card sales at Bank Mandiri KCP Darmo Indah Surabaya remain relatively low. Therefore, this research aims to analyze marketing strategies for Bank Mandiri’s credit card products using a SWOT analysis. This research employs a descriptive qualitative approach by elaborating data obtained from interviews and observations conducted with employees of Bank Mandiri KCP Surabaya Darmo Indah. Based on the research findings, it is revealed that SWOT-based marketing strategies can be applied to improve sales by leveraging product strengths and market potential, such as establishing partnerships with various institutions, collaborating with different brands, and highlighting the QRIS feature on credit cards, while minimizing weaknesses and challenges through measures such as annual fee waivers, interest rate discounts, and cashback programs. The findings of this study can be applied to enhance existing marketing strategies in order to maximize product sales.